Predictors of Failed and Delayed Decannulation after Head and Neck Surgery. (September 2016) - Isaac, Andre; Zhang, Han; Varshney, Samarth; Hamilton, Stefan; Harris, Jeffrey R.; O'Connell, Daniel A.; Biron, Vincent L.; Seikaly, Hadi
Objective: To determine the variables that are predictive of failed decannulation (FD), delayed decannulation (DD), and days to decannulation in patients who underwent head and neck cancer resection with free tissue transfer reconstruction for head and neck squamous cell carcinoma. Design: Case series with chart review. Setting: Tertiary care otolaryngology–head and neck surgery referral center. Subject and Methods: Patients (N = 108) were included who underwent head and neck cancer resection with free tissue transfer reconstruction and tracheostomy between 2011 and June 2014. Patients with laryngectomy, previous tracheostomy, and other airway pathology necessitating tracheotomy were excluded. Preoperative patient variables and cancer site/staging variables were analyzed, as well as extent of structures resected and type of reconstruction. Univariate and multivariate binary logistic and Cox regression analyses were used to determine predictors of FD and DD. Cox regression analysis was used to determine predictors of days to decannulation. Results: Of the 108 included patients, 16 had FD, and 26 had DD. Univariate analysis demonstrated that advanced stage ( r = 0.233, P = .021), total glossectomy ( r = 0.924, P < .001), anterolateral thigh flap reconstruction ( r = 0.906, P < .001), smoking at time of surgery ( r = 0.319, P = .002), and pack years ( r = 0.322, P = .001) were associated with FD. Cox regression analysis showed that total glossectomy, exp(B) = 15.837 (95% confidence interval [95% CI]: 1.949-128.679); anterolateral thigh flap reconstruction, exp(B) = 8.439 (95% CI: 2.435-29.620); and smoking status, exp(B) = 2.970 (95% CI: 1.617-5.456) were independent predictors of days to decannulation and FD. Conclusions: Patients with total glossectomy defects and those who continue to smoke are at increased risk for FD and DD. Aggressive smoking cessation programs may decrease the risk of FD and DD. Patients should be counseled about their risk profiles.